The Effect of Covid 19 on Tbc Patient Visits - Fachrul Suarli (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Pulmonary tuberculosis is a disease that is of concern to the world, especially Indonesia which is in the third-highest rank after India and China. Some studies have reported that patients living with tuberculosis and who are undergoing anti-tuberculosis drug therapy have a significant impact on their quality of life. TB patients who are undergoing treatment, both obedient and non-compliant can experience a decrease in various physical, social, psychological, and environmental functions which will have an impact on decreasing quality of life. However, since 2019, there has been a Covid-19 pandemic which is highly contagious and can cause severe illness, causing people to be afraid to come to health facilities. Because people are afraid to come to health facilities, it is feared that there will be an explosion of TB disease because of the risk of dropping out of drugs which causes an increase in the death rate due to TB. In addition, without treatment for TB patients, it can cause the spread of TB disease to become more widespread. So if a TB patient suffers from Covid-19, it can make his illness worse. During the COVID-19 pandemic, WHO estimates that there will be a 25% reduction in TB case detection.